2005
DOI: 10.1161/circulationaha.104.516757
|View full text |Cite
|
Sign up to set email alerts
|

Multitargeted Effects of Statin-Enhanced Thrombolytic Therapy for Stroke With Recombinant Human Tissue-Type Plasminogen Activator in the Rat

Abstract: Background-Microvascular dysfunction posttreatment of stroke with recombinant human tissue-type plasminogen activator (rht-PA) constrains the therapeutic window to 3 hours. Statins (3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors) promote vascular thrombolysis and reduce the inflammation response. We therefore investigated the neuroprotective effects of a combination of atorvastatin and delayed rht-PA treatment in a rat model of embolic stroke. Methods and Results-Rats subjected to embolic middle ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
86
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 34 publications
10
86
0
1
Order By: Relevance
“…5 Following plaque disruption, statins promote vascular fibrinolysis by exerting various inhibitory actions on platelet deposition and aggregation, coagulation factors, and rheology. 14,15 However, our study found no significant difference in the coronary artery reperfusion rate as assessed by initial TIMI flow grade after fibrinolytic therapy between patients with and without statin pretreatment.…”
Section: Statins and Fibrinolysismentioning
confidence: 99%
See 1 more Smart Citation
“…5 Following plaque disruption, statins promote vascular fibrinolysis by exerting various inhibitory actions on platelet deposition and aggregation, coagulation factors, and rheology. 14,15 However, our study found no significant difference in the coronary artery reperfusion rate as assessed by initial TIMI flow grade after fibrinolytic therapy between patients with and without statin pretreatment.…”
Section: Statins and Fibrinolysismentioning
confidence: 99%
“…2,3 Statins also reduce hemostasis by inhibiting platelet activation and the procoagulation cascade, and by augmenting the anticoagulation cascade. 4 Thus, statins appear to effectively enhance the fibrinolytic activity of t-PA. An experimental study in animals has shown that combination treatment with a statin and t-PA after stroke increases cerebral blood flow and reduces infarct volume as compared with fibrinolytic treatment alone; 5 however, data in humans are lacking. Prompt reperfusion of the occluded artery is crucial to limiting the size of an infarct.…”
mentioning
confidence: 99%
“…44,45 Combination atorvastatin and recombinant human tissue plasminogen activator (rhtPA) treatment 4 hours after stroke induces downregulation of tissue factor, protease-activated receptor 1, intercellular adhesion molecule 1, and matrix metalloproteinase 9 (MMP 9); concomitantly, it reduces cerebral microvascular thrombosis and enhances microvascular integrity. 46 Patients who had taken statins prior to the onset of stroke have significantly decreased mortality and improved outcome after acute ischemic stroke. 47,48 The results of the recently reported in stroke prevention by aggressive reduction in cholesterol levels (SPARCL) trial indicate that atorvastatin is likely efficacious in reducing the incidence of recurring stroke.…”
Section: Pharmacological Treatment Of Stroke Statinsmentioning
confidence: 99%
“…Semiquantitative measurements of immunoreactive cells were performed, according to our previously published methods (Zhang et al, 1999(Zhang et al, , 2005a. Briefly, immunoreactive cells in the nonstroke and stroke SVZ were digitized under a 40 Â objective (BX40; Olympus Optical) using a 3-CCD color video camera (DXC-970MD; Sony, Tokyo, Japan) interfaced with an MCID image analysis system.…”
Section: Quantificationmentioning
confidence: 99%